Effect of nitrogen on root morphology, shoot physiology and yield of contrasting rice (Oryza sativa) genotypes - Tan, Beverly Mei Chin (2016)
Rice plant (Oryza sativa) is a major cereal crop greatly consumed worldwide, and thus plays an essential role in achieving global food security. Since nitrogen is an essential nutrient required by all crops to achieve superior growth and yield, determination of the optimum nitrogen fertilisation amount required for different rice genotypes to achieve optimal yield production as well as root and shoot growth is crucial. In light of increasingly severe global warming, there is an urgent need to study root morphology of rice plants which plays a major role in resisting drought. The objectives of this study is to determine the optimal amount of nitrogen fertilisation required for optimal yield production, root and shoot growth in two Malaysian rice genotypes (MR220 and MR263), as well as to investigate difference between the genotypes in response to nitrogen fertilisation. The two rice genotypes were subjected to different nitrogen treatment levels (0, 60, 120 and 180 kgha-1), in two splits: during tillering initiation and panicle initiation. The data on nitrogen treatment effect on vegetative and dry weight parameters (chlorophyll content, total leaf area, root morphology, shoot and root dry weight) were then collected at active panicle development and flowering stage; while grain and dry weight parameters (grain weight, harvest index, total number of spikelets per panicle, spikelet fertility, shoot and root dry weight) were collected at maturity. Nitrogen treatment was found to have a significant effect on shoot physiology, root morphology and yield of both the rice genotypes, with optimal nitrogen application rates ranging from 60 to 120 kgha-1. As for differences between genotypes under nitrogen fertilisation condition, MR220 produced significantly higher shoot dry weight, average root diameter and root dry weight as compared to MR263; while MR263 produced root system that was more efficient in nutrient and water scavenging due to significantly higher total root length and surface area as compared to MR220. This study had provided an insight in role of nitrogen in affecting yield, root and shoot growth in rice plants, as well as genotypic differences between different rice genotypes in response to nitrogen fertilisation. As such, it can be concluded that proper nitrogen management and fertilisation in cropping systems is required for optimal growth and yield of different rice genotypes.